PENGARUH DOSIS PUPUK BIO SLURRY CAIR DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MENTIMUN (Cucumis sativus L.) - Masitoh, Wirianti; Puspitorini, Palupi; Widiatmanta, Jeka (Universitas Islam Balitar, 2018)
This study aims to determine the effect of liquid organic fertilizer on the growth andyield of cucumber plants, to determine the effect of applying spacing on the growth and yield ofcucumber plants, to determine the interaction of liquid bio slurry fertilizer and spacing ongrowth and yield of cucumber plants. The study was conducted using a randomized block designarranged in factorial (RAK) with 2 factors, the first factor was a liquid bio slurry fertilizer (P)dose consisting of 3 levels, 40 l / ha-1 (P1), 80 l / ha- 1 (P2), 120 l / ha-1 (P3). The second factoris the spacing (J) consisting of 3 levels: 30x60 cm (J1), 40x60 cm (J2), 50x60 cm (J3), 60x60 cm(J4). The variables observed included stem diameter, leaf area, and total weight. Data wereanalyzed using analysis of variance (ANOVA) level of 5% and further testing with Duncan 'sMultiple Range Test (DMRT). The results showed: By giving different liquid slurry bio fertilizerdoses gave a significant effect on the leaf area of cucumber plants at the age of 21 HSTobservations. The best treatment for organic fertilizer dosage is in the treatment of 120 L ha -1(P3). The application of spacing has a significant effect on the stem diameter variable at the ageof 28 HST observations, and on leaf area variables at all ages of observation. The best treatmentof spacing on the variable stem diameter and leaf area on the treatment spacing of 60x60 cm(J4). There were no significant interactions on the treatment of liquid bio slurry fertilizer dosesand the spacing of growth and yield of cucumber plants at all ages of observation.